India’s 2014 general elections: a critical realignment in Indian politics? - Mitra, Subrata Kumar; Schöttli, Jivanta (Asian survey, 2016)
Phrases like “watershed,” “historic,” and “epochal” were used to describe India’s 2014 general election. The Bharatiya Janata Party secured the first single-party majority in three decades, forming the government as the National Democratic Alliance. We argue that the 16th Lok Sabha elections marked a realignment, not a clean break with the past.